Knowledge, attitude and practice towards use of herbal aphrodisiac among unani & ayurvedic health care seekers in Dhaka city (Asian Journal of Medical and Biological Research, 2018)
Geographically Bangladesh is the treasure-house of medicinal plants especially herbal aphrodisiac medicines. The World Health Organization (WHO) reported that 70%–80% of the global population relies on herbs for primary health care. Sexual health is a state of complete physical, mental and social well-being in all aspects related to the reproductive system. The study aimed as assessing the use of herbal aphrodisiac among Unani & Ayurvedic health care seekers in Dhaka city, knowledge, attitude and practice. The study design was a descriptive cross-sectional study. This study was conducted at Unani and Ayurvedic Medical College Hospital among 220 patients at Mirpur-13, Dhaka using a semi-structured interviewed questionnaire. The study result depicted that 47.7% respondents were in 21-30 years age group. The mean age was 31.22±8.265 years and the range was from 17-50 years. It was found that the prevalence of Premature Ejaculation (PE) and Erectile Dysfunction (ED) was 26.4% and 21.8% respectively. Low level of knowledge was found about different aspects of Unani and Ayurvedic System of Medicine. It was revealed that most of the respondents (95%) knew about the very effective aphrodisiac, their safety and cost issue. It was also revealed that most (79.1%) of the respondents strongly opined about less side-effect of herbal aphrodisiac. The study findings suggest that there is a significant association between age and knowledge about Govt. teaching hospital and between education and knowledge about cost of aphrodisiac in herbal medicine.Asian J. Med. Biol. Res. December 2018, 4(4): 400-405